2012
DOI: 10.3858/emm.2012.44.7.049
|View full text |Cite
|
Sign up to set email alerts
|

Synergy between adiponectin and interleukin-1β on the expression of interleukin-6, interleukin-8, and cyclooxygenase-2 in fibroblast-like synoviocytes

Abstract: To determine whether adiponectin may have synergistic effects in combination with the proinflammatory cytokine interleukin (IL)-1β regarding the production of proinflammatory mediators during arthritic joint inflammation, synovial cells from rheumatoid arthritis (RA) patients were treated with adiponectin, IL-1β, and their combination for 24 h. Culture supernatant was collected and analyzed by enzyme-linked immunosorbent assay for levels of IL-6, IL-8, prostaglandin E2 (PGE2), vascular endothelial growth facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 28 publications
(38 reference statements)
3
36
1
1
Order By: Relevance
“…This discrepancy may result from the application in our experiments of adiponectin isoforms instead of native adiponectin and higher, but still physiologically relevant, concentrations of IL-1β. Although the synergistic effect was associated with the up-regulation of FLS receptors for IL-1 and adiponectin, no synergy in the production of MMPs was observed (13). The latter observation is consistent with the results of our current study (Figure 2).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This discrepancy may result from the application in our experiments of adiponectin isoforms instead of native adiponectin and higher, but still physiologically relevant, concentrations of IL-1β. Although the synergistic effect was associated with the up-regulation of FLS receptors for IL-1 and adiponectin, no synergy in the production of MMPs was observed (13). The latter observation is consistent with the results of our current study (Figure 2).…”
Section: Discussionsupporting
confidence: 93%
“…In vitro data suggest that adiponectin contributes to joint inflammation and destruction. Some reports have demonstrated that, at a concentration of 10 μg/mL, adiponectin increases the production of pro-inflammatory cytokines, chemokines, growth factors, and MMPs to levels lower than (IL-6, IL-8) or similar to (MMP-1, MMP-13, VEGF) the level triggered by 0.1-10 ng/mL of IL-1β (12,13). Moreover, at a very high (25 μg/mL) concentration, adiponectin was reported to up-regulate the expression of numerous genes/proteins relevant to RA pathogenesis (e.g.…”
Section: Discussionmentioning
confidence: 98%
“…For example, IL-1b was reported to be a potent inducer of other cytokines, including IL-8 or CCL2. [40][41][42] We found glomerular monocyte accumulation, significantly elevated renal IL-1b levels, and pharmacological IL-1 receptor blockade that protected Phox-deficient mice from NCGN, making Phoxdysregulated IL-1b generation an attractive candidate mechanism for disease acceleration. In the presence of ANCA, Phox deficiency caused accelerated monocyte caspase-1 activity and increased IL-1b generation in vitro.…”
Section: Discussionmentioning
confidence: 98%
“…Briefly, BV2 cells (1 × 10 5 cells/mL) were plated in 24-well plates and pre-treated with the indicated concentrations of anthocyanins for 1 h before treatment with 0.5 μg/mL LPS for 24 h. One hundred microliters of culture-medium supernatants was collected to determine IL-1β, and TNF-α concentrations by ELISA [45]. …”
Section: Methodsmentioning
confidence: 99%